1983
DOI: 10.1016/s0140-1971(83)80056-6
|View full text |Cite
|
Sign up to set email alerts
|

Sex and personality differences in self‐reported social skills among British adolescents

Abstract: Despite the fact that a considerable amount of research has been done, both in America and Britain, on social skills training and assessment, few studies have looked at either sex differences or personality correlates of social skills. A homogeneous group of over 200 normal British adolescents were administered a standard British personality and social skills questionnaire. Although there seemed very little evidence of sex differences in self‐reported social anxiety, two personality variables—extraversion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0
2

Year Published

1986
1986
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 23 publications
3
6
0
2
Order By: Relevance
“…Figure 1. The present results also accord with the fact that higher P scores tend to be associated with a range of problem behaviours (Furnham & Gunter, 1983;Gudjonsson, 1997). respect to each of the dependent measures.…”
Section: Discussionsupporting
confidence: 90%
“…Figure 1. The present results also accord with the fact that higher P scores tend to be associated with a range of problem behaviours (Furnham & Gunter, 1983;Gudjonsson, 1997). respect to each of the dependent measures.…”
Section: Discussionsupporting
confidence: 90%
“…The positive correlation of asocial behavior with psychoticism is congruent with the description of this variable (Eysenck & Eysenck, 1975). Furnham and Gunter (1983) found that adolescents with high psychoticism scores tend to report social difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Respecto a la relación con variables de personalidad, los adolescentes introvertidos e inestables emocionales informan mayores dificultades interpersonales, del mismo modo que en otras investigaciones con adolescentes americanos (Rolf, 1972), británicos (Furnham, 1984;Furnham y Gunter, 1983), canadienses (Young y Bradley, 1998), y españoles (Gismero, 2000, Silva y Martorrell, 1987.…”
Section: Discussionunclassified
“…La investigación revela que los adolescentes con dificultades interpersonales se perciben menos asertivos (Beidel, Turner y Morris, 1995;Clark, et al, 1994;Crozier, 1995;García-López, Olivares, Hidalgo, Beidel y Turner, 2001), se valoran con menos capacidad para relacionarse con el otro sexo (Clark eí al., 1994;Inglés et al, 2000;La Greca y López, 1998), experimentan más miedo a hablar en público (Essau et al, 1999;Inglés eí al., 1999Inglés eí al., , 2000Martínez, Méndez, Hidalgo e Inglés, 1999), informan menos aceptación y apoyo de su grupo de compañeros (Inderbitzen et al, 1997;Walters e Inderbitzen, 1998), y presentan relaciones más conflictivas con los padres (Openshaw eí al., 1992). Por otro lado, también se ha hallado con muestras adolescentes que las dificultades interpersonales correlacionan positivamente con introversión y neuroticismo (Furnham, 1984;Furnham y Gunter, 1983;Gismero, 2000;Rolf, 1972;Silva y Martorell, 1987;Young y Bradley, 1998). Por tanto, se plantean las hipótesis de que los adolescentes con fobia social generalizada, miedo a hablar en público, introvertidos, inestables emocionales, presentan mayores dificultades interpersonales que los adolescentes sin fobia social generalizada, sin miedo a hablar en público, extravertidos, estables emocionales.…”
unclassified